Analisis E-commerce Dalam Membantu Penjualan UMKM di Tengah Pandemi - Nadia Ika Purnama; Linzzy Pratami Putri; Rahmad Bahagia (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
Micro, Small and Medium Enterprises (MSMEs) are business ventures that have a very negative impact due to the COVID-19 pandemic. This impact is caused by a decrease in the level of public consumption. MSMEs must survive by finding solutions to reduce consumer consumption and make consumers' lifestyles more digital. E-commerce is an electronic commerce that includes sales and purchases transactions made online without meeting each other. E-commerce plays an important role in helping MSMEs to survive during the pandemic and continue to carry out their sales activities even though they are hindered by massive social barriers. This research is a qualitative descriptive research that explains phenomena and data and previous research, then draws conclusions from the existing problems. From the discussion, it can be said that the role of e-commerce in helping MSMEs during the pandemic is to increase MSME income, increase MSME sales, and as a marketing strategy and media promotion for MSMEs.